Guiding the long way to broad HIV neutralization. Issue 3 (May 2017) - Peterhoff, David; Wagner, Ralf
Abstract : Purpose of review: It has been demonstrated that extensive virus diversification and antibody coevolution are necessary to give rise to broadly neutralizing antibodies targeting the envelope protein of HIV-1. Here, we discuss recent progress of vaccine design approaches aiming on strategies to initiate and guide B-cell development toward this outcome, as well as their evaluation in mouse models engineered to express human antibodies. Recent findings: Several specially tailored transgenic mouse strains have been developed to test the concept of engaging and guiding B-cell development by sequential immunizations. Currently available models display prerearranged or nonrearranged germline or mature VDJH and VJL loci of CD4-binding-site-specific (VRC01, 3BNC60) and high-mannose-patch-specific (PGT121) broadly neutralizing antibodies, or even the complete human V(D)J segments. Data generated in these knock-in mouse models elegantly prove the feasibility of the concept when using a carefully selected panel of engineered envelope proteins. Summary: Recent studies in knock-in transgenic mouse models provide a proof-of-concept that germline B-cell receptor targeting followed by sequential immunization can engage the respective naïve precursor B cells and guide B-cell receptor development toward broadly neutralizing reactivity.